Pelatihan Penerapan PP No 23 Tahun 2018 dan Aspek Perpajakannya di Lingkungan SMKN 44 Jakarta Pusat - Agustina Indriani; Ahmad Basid Hasibuan; Jombrik TPR; Sri Ari Wahyuningsih (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of implementing the service is to provide a broader understanding to the community, especially to students in the SMKN 44 Central Jakarta environment. With this activity, students/trainees have skills that can be used if they want to work after graduating from SMKN. This training on taxation is indeed very important and needed at this time by teachers and students at SMKN 44 Central Jakarta where the material provided is up to date taxation in accordance with current government regulations including incentives provided by the government in conditions the Covid-19 pandemic. The results of this training also obtained an illustration that socialization of taxation for MSMEs must continue to be carried out by related parties so that all levels of society can understand and understand their tax obligations. The implementation of this learning shows that the enthusiasm of students and teachers for the material presented is quite high and it is very much needed for students and teachers, it is proven that many participants ask questions about the material presented and taxation in general, but due to time constraints so not all of the participants' questions can be answered one by one. This can be interpreted that the participants listened carefully to all the material presented.